2014
DOI: 10.1371/journal.pone.0098313
|View full text |Cite
|
Sign up to set email alerts
|

Niacin in Pharmacological Doses Alters MicroRNA Expression in Skeletal Muscle of Obese Zucker Rats

Abstract: Administration of pharmacological niacin doses was recently reported to have pronounced effects on skeletal muscle gene expression and phenotype in obese Zucker rats, with the molecular mechanisms underlying the alteration of gene expression being completely unknown. Since miRNAs have been shown to play a critical role for gene expression through inducing miRNA-mRNA interactions which results in the degradation of specific mRNAs or the repression of protein translation, we herein aimed to investigate the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Less is known about potential regulatory roles of other vitamins, including those that function as true enzyme cofactors in the metabolic network. However, gene expression profiling in mammalian cells has revealed transcript-level responses to vitamins B1 (thiamine) ( Fraser et al, 2012 ; Liu et al, 2004 ) ( Tanaka et al, 2007 ), B2 (riboflavin) ( Nakano et al, 2011 ), B3 (nicotinamide/niacin) ( Choi et al, 2011 ; Couturier et al, 2014 ; Giammona et al, 2006 ), B6 (pyridoxal 5′ phosphate, PLP) ( Toya et al, 2012 ; Zhang et al, 2014 ), B9 (folic acid) ( Barua et al, 2014 ; Champier et al, 2012 ; Lin et al, 2011 ), C (ascorbic acid) ( Canali et al, 2014 ; Jun et al, 2011 ; Takahashi et al, 2014 ), and E (tocopherol/tocotrienols) ( Landrier et al, 2010 ; Makpol et al, 2013 ; Mustacich et al, 2009 ). The mechanisms behind, and consequences of, these observed vitamin-induced gene expression changes have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about potential regulatory roles of other vitamins, including those that function as true enzyme cofactors in the metabolic network. However, gene expression profiling in mammalian cells has revealed transcript-level responses to vitamins B1 (thiamine) ( Fraser et al, 2012 ; Liu et al, 2004 ) ( Tanaka et al, 2007 ), B2 (riboflavin) ( Nakano et al, 2011 ), B3 (nicotinamide/niacin) ( Choi et al, 2011 ; Couturier et al, 2014 ; Giammona et al, 2006 ), B6 (pyridoxal 5′ phosphate, PLP) ( Toya et al, 2012 ; Zhang et al, 2014 ), B9 (folic acid) ( Barua et al, 2014 ; Champier et al, 2012 ; Lin et al, 2011 ), C (ascorbic acid) ( Canali et al, 2014 ; Jun et al, 2011 ; Takahashi et al, 2014 ), and E (tocopherol/tocotrienols) ( Landrier et al, 2010 ; Makpol et al, 2013 ; Mustacich et al, 2009 ). The mechanisms behind, and consequences of, these observed vitamin-induced gene expression changes have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, niacin has recently been shown to alter gene expression, including factors involved in Wnt signaling, in skeletal muscle of obese Zucker rats (Couturier et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a single miRNA can regulate hundreds of protein-encoding target mRNAs, indicating the great regulatory potential of miRNAs (Bartel, 2004). We recently demonstrated in a study with rats that NA at a pharmacologic dosage alters the expression of miRNAs in skeletal muscle, and in silico target gene prediction indicated that more than 1,800 mRNAs are putative targets of NA-regulated miRNAs (Couturier et al, 2014). Moreover, we showed that many of the predicted target mRNAs from the most strongly downregulated miRNAs are involved in transcription regulator activity and regulation of transcription from RNA polymerase, indicating that processes dealing with gene transcription are activated by NA treatment because the mRNAs from downregulated miRNAs are less targeted and, thus, less degraded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that many of the predicted target mRNAs from the most strongly downregulated miRNAs are involved in transcription regulator activity and regulation of transcription from RNA polymerase, indicating that processes dealing with gene transcription are activated by NA treatment because the mRNAs from downregulated miRNAs are less targeted and, thus, less degraded. Interestingly, the recent rat study also showed that several stressresponsive transcription factors including ATF3, ATF1, and one member of the E2F family, E2F7, are targets of the miRNAs downregulated by NA (Couturier et al, 2014). In the liver of cows fed rumen-protected NA, 831 mRNAs were predicted as targets of the 10 most strongly downregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%